2013
DOI: 10.1111/dom.12216
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent decline of β‐cell function in type 1 diabetes after diagnosis: a multi‐centre longitudinal study

Abstract: This study reveals a positive correlation between age at diagnosis of type 1 diabetes and FCP with a more rapid decline of β-cell function in the very young patients. These data can inform the design of clinical trials using C-peptide values as an end-point for the effect of a given treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
92
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 41 publications
18
92
2
4
Order By: Relevance
“…Similarly, combined data from TrialNet studies described insulin secretion in adults and pediatric subjects entered in type 1 diabetes clinical trials, but only within 2 years of diagnosis (8). As in our current study, Barker et al (15) reported differences in C-peptide according to age at diagnosis. While involving a large number of subjects, that study involved only subjects within 5 years of diagnosis and used noncentralized measurements of fasting Cpeptide.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, combined data from TrialNet studies described insulin secretion in adults and pediatric subjects entered in type 1 diabetes clinical trials, but only within 2 years of diagnosis (8). As in our current study, Barker et al (15) reported differences in C-peptide according to age at diagnosis. While involving a large number of subjects, that study involved only subjects within 5 years of diagnosis and used noncentralized measurements of fasting Cpeptide.…”
Section: Discussionsupporting
confidence: 73%
“…This study included a highly selective cohort of survivors from an era prior to present management paradigms and thus may not be characteristic of a general, current type 1 diabetes population. Others have also reported on the presence of residual insulin secretion in type 1 diabetes; these studies tested selected cohorts (11)(12)(13), small numbers of participants (14), or individuals with a limited duration of disease (15). In addition to the presence of diabetes-related autoantibodies, history of other autoimmune diseases, and family history of type 1 diabetes, the absence or presence of endogenous insulin secretion is often used to classify patients as having type 1 diabetes versus type 2 diabetes.…”
mentioning
confidence: 99%
“…Rapid weight gain during the first years of life has been found to increase the incidence of type 1 diabetes (7) and a number of studies have also shown a positive correlation between the year of onset of type 1 diabetes and BMI (8,9,10). More recently, we have shown that the decline in fasting C-peptide is more rapid in those patients with an earlier age of onset of type 1 diabetes, and that the factors influencing the decline in fasting C-peptide following diagnosis differ substantially according to the age of onset (11). Several studies have reported data showing that the age of onset of type 1 diabetes is inversely related with BMI, with children diagnosed at younger ages typically being heavier than those diagnosed later (9,12,13,14).…”
Section: Introductionmentioning
confidence: 67%
“…In each study centre, type 1 diabetes was diagnosed according to ADA and WHO criteria. A detailed description of the cohort has been published elsewhere (11).…”
Section: Subjectsmentioning
confidence: 99%
“…Classic type 1 diabetes clinical progression is thought to eventually reach a state of absolute insulin deficiency, and the rate at which this state is reached is dependent on many factors, most notably glycemic control and age at onset; however, more literature on long-term insulin microsecretors is emerging (2,3,10). We wondered why this patient had such severe comorbidities, presumed rapid disease progression, and early death despite the presence of insulin-positive b-cells, appreciable C-peptide, and HLA associated with protection against type 1 diabetes.…”
mentioning
confidence: 99%